2008
DOI: 10.1007/s10531-008-9428-y
|View full text |Cite
|
Sign up to set email alerts
|

Diet breadth, coexistence and rarity in bumblebees

Abstract: Factors that determine the relative abundance of bumblebee species remain poorly understood, rendering management of rare and declining species difficult. Studies of bumblebee communities in the Americas suggest that there are strong competitive interactions between species with similar length tongues, and that this competition determines the relative abundance of species. In contrast, in Europe it is common to observe several short-tongued species coexisting with little or no evidence for competition shaping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
103
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 47 publications
8
103
0
1
Order By: Relevance
“…The strong preference of bumble bees for Fabaceae also agrees with results from previous studies (Goulson and Darvill 2004;Goulson et al 2005Goulson et al , 2008aConnop et al 2010;Redpath et al 2010). Fabaceae seem thus to be highly important for bumble bees, especially for longer-tongued species, such as B. hortorum (19 visits to Fabaceae in this study, 47.5 %), B. lapidarius (68 visits, 52.3 %), and B. pascuorum (76 visits, 32.2 %).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The strong preference of bumble bees for Fabaceae also agrees with results from previous studies (Goulson and Darvill 2004;Goulson et al 2005Goulson et al , 2008aConnop et al 2010;Redpath et al 2010). Fabaceae seem thus to be highly important for bumble bees, especially for longer-tongued species, such as B. hortorum (19 visits to Fabaceae in this study, 47.5 %), B. lapidarius (68 visits, 52.3 %), and B. pascuorum (76 visits, 32.2 %).…”
Section: Discussionsupporting
confidence: 91%
“…Note that all bumble bees observed in our study belong to species commonly found in and outside of cities (Goulson et al 2005(Goulson et al , 2008a; Banaszak-Cibicka and Żmihorski 2012), while typically rare species, such as B. sylvarum L. or B. humilis Illiger, were not observed in our study. Consequently, there are most likely Bwinners and losersô f urbanization (Banaszak-Cibicka and Żmihorski 2012).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…), Bombus lapidarius (L.), B. ruderarius (Müller), B. terrestris (L.)]. Bombus species recorded during the experiment represented two tongue-length classes (shorttongued B. terrestris and B. lapidarius and medium-tongued B. ruderarius; Goulson et al 2008b), and we, however, observed no significant differences in performance among these species and therefore in subsequent analyses treat them together as one functional group. Bumblebees made over 81 % of the visits, Andrena made 13 % and A. plumipes 6 % (the latter, for simplicity, hereafter referred to as Anthophora).…”
Section: Resultsmentioning
confidence: 85%
“…Consequently, the only reliable information we have on the ecology of these three species comes from Murray et al (2008) and Stanley et al (2013) who used molecular methods to study the lucorum complex in Ireland and Waters et al (2010) who studied them in the Western Isles of Scotland. Niche-partitioning might be expected between these species (Goulson et al, 2008b) and indeed some ecological differences have been suggested. Specifically, Waters et al (2010) found that B. magnus appeared to be strongly associated with the heathland forage plant Calluna vulgaris.…”
Section: Introductionmentioning
confidence: 94%